Factors influencing consumers’ purchase intention towards Takaful Ikhlas products in Kuala Lumpur / Mohd Mustaqim Mustaffa - Mustaffa, Mohd Mustaqim (Faculty of Business and Management, 2011)
Consumers’ purchase intention is very important to Takaful Ikhlas Company. The main objective of Takaful Ikhlas is to increase their profit, so by doing this study the researcher will determine what are the factors influencing consumers’ purchase intention towards Takaful Ikhlas products. These factors are very valuable for the company to know their consumers’ and build new business development. In addition it is very important to plan new strategist to achieve business target. This research also important to future researcher to refer and learn about the consumers’ purchase intention. Lastly, the data that being used by the researcher is primary and secondary data. The data being analyze and the researcher make conclusion and recommendation.